Relation Between Transport Distance with Frequency-Dependent Volume Magnetic Susceptibility in Surabaya River Sediments - Mariyanto Mariyanto; Ayi Syaeful Bahri; Widya Utama; Wien Lestari; Linda Silvia; Titis Lestyowati; Muhammad Khayrul Anwar; Wahyu Ariffiyanto; Ahmad Irfaan Hibatullah; Moh Faisal Amir (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
Volume magnetic susceptibility measurements have been widely used in numerous studies related to river sediment characterization. A study of the transport distance effect toward the frequency-dependent volume magnetic susceptibility is needed to identify the superparamagnetic grain behavior in river sediments. The purpose of this study is to identify the presence of superparamagnetic grains and to obtain the relation between transport distances and frequency-dependent volume magnetic susceptibility in river sediments. The sediment samples were taken and measured by using the Bartington MS2B Susceptibilitymeter at two different frequencies of 470 Hz and 4700 Hz. The measurement results show that the sediment transport distance is directly proportional to the frequency-dependent volume magnetic susceptibility. Superparamagnetic grain content is identified to tend to be higher as the distance of sediment transport increases.